Peningkatan Hasil Belajar Siswa Dengan Media Gambar Pada Mata Pelajaran Akidah Akhlak: Indahnya Kalimat Tayyibah - Adawiyah, Rabiatul; Inayati, Mahfida; Hufron, A (Jumper: Journal of Educational Multidisciplinary Research, 2024)
This study aims to determine the influence of the use of image media in improving student learning outcomes in the subject of Akidah Akhlak, the exquisite material of class IV thayyibah sentences at MIS AL IMRON Pakamban Laok Sumenep for the 2023/2024 academic year. This research is a class action research (PTK). The subjects in this study were grade IV students at MIS AL IMRON Pakamban Laok totaling 11 people. This research is carried out in 2 cycles consisting of four stages, namely planning, implementation, observation and reflection. The data collection techniques used are tests, observation and documentation. The results showed that learning outcomes improved in each cycle. In the first cycle, the percentage of classical completeness was 63.63% with an average score of 76.18% and the completeness of new students reached low-level work indicators from research and student learning classifications were categorized as sufficient. Meanwhile, in cycle II the percentage of classical completeness was 90.90% with an average value of 83.13%, in cycle II the percentage of student learning activities was 85% categorized as good. The conclusion in this study is that the use of image media can improve student learning outcomes in the subject of Akidah Akhlak, the exquisite material of thayyibah sentences in class IV MIS AL IMRON Pakamban Laok Sumenep.